Neologism and Terminography in the Arabic Translation of Pierre Joseph Macquer’s Art de la Teinture en Soie - Massa, Marianna (TTR)

(untitled) (Association canadienne de traductologie, 2025)
This article explores patterns of neologism formation in the field of Arabic scientific terminology during the 19th century by examining the translation of Pierre Joseph Macquer’s Art de la Teinture en Soie (1763), published in Arabic as Kitāb fī Ṣināʿat Ṣibāġat al-Ḥarīr in 1823. The first sections of the article summarize the historical, political, and industrial context in which this translation emerged in order to contextualize the work carried out by the translator of Macquer’s treaty, Don Raphaël de Monachis, within the broader framework of the nahḍa [Arab Renaissance]. This was a period a marked by intense translation activity, particularly from French into Arabic, as part of the Egyptian ruler Muḥammad ʿAlī Bāšā’s modernization reforms. The last section of the article offers a detailed linguistic analysis of the terminological strategies adopted by de Monachis. Drawing on a comparison of the French terms included in Art de la Teinture en Soie and the Arabic equivalents, the article identifies multiple translation techniques, including derivation [ištiqāq], Arabization [taʿrīb], semantic calques, literal translations, hybrid compounds, and the use of vernacular expressions. It highlights specific cases such as the use of (qābil li-, “capable of”) to render adjectives like miscible or extractive, and نزع (nazʿ, “removal”) to express French prefixes such as dé- and dis- in terms like dégommage and disbroder. Finally, the article argues that Don Raphaël de Monachis should be considered one of the first modern Arabic terminographers. His translation of Macquer’s work laid important groundwork for the terminological efforts that would characterize the broader nahḍa movement. His role as a translator extended beyond linguistic transfer: he was a linguistic innovator and mediator between epistemological systems.